Revisiting African Spirituality: A reference to Missiological Institute consultations of 1965 and 1967 - Mashabela, James K. (HTS teologiese studies, 2024)
This article revisits the hope of the First and Fourth Missiological Institute (MI) consultations in 1965 and 1967 regarding the survival of African Spirituality as relevant to the daily life of South African churches. African Spirituality has played a significant role in the cultural context of Africans. In the African context, African Spirituality is intertwined with life, death, and health, which co-exist with material aspects and the economy as gracious gifts from God. The churches in South Africa and elsewhere in Africa have been challenged by the African worldview of healing and culture. Thus, Africans mostly prefer the African-centred church with more African Christianity, instead of Western Christianity. This has been a serious challenge in African church circles for centuries, even in the current 21st century. The question therefore arises whether this is a matter for the Africanisation, indigenisation, and decolonisation of the church in Africa.Contribution: The article analyses the two MI consultations and whether the church in the 21st century has Africanised and decolonised itself in service of its African members. The study is a historical approach given the history of the MI’s contribution in South Africa. The concept of African Spirituality is unpacked and contextualised within the African Independent Churches’ (AIC) Zionist type churches such as the Zion Christian Church (ZCC), the St John’s Apostolic Faith Mission (AFM), and other Ethiopian type churches such as Lutheran Bapedi Church and others in South Africa and African Traditional Religions (ATR). The article engages the importance of how African Spirituality differs from other spiritualities within the context of Christian spirituality.